A composite adsorption-photocatalyst and preparation method thereof
By doping Fe and O and P elements into graphene-like carbon nitride, the visible light response range and electron transfer efficiency of the photocatalyst are improved, the problem of insufficient activity of existing photocatalysts is solved, and high-efficiency treatment of high-salt organic wastewater is achieved. antibiotic contaminants in it.
Patent Information
- Application Number
- CN202310496034.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-05
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2043-05-05
AI Technical Summary
The existing graphene-like carbon nitride photocatalysts have a narrow visible light response range in high-salt organic wastewater, low separation efficiency of photogenerated electron-hole pairs, and low interfacial charge transfer efficiency, resulting in insufficient catalytic activity.
By co-doping metal elements Fe and non-metal elements O and P to graphene-like carbon nitride, adjusting the electronic structure, enhancing the photogenerated electron transfer efficiency and visible light response range, a composite adsorption-photocatalyst was prepared.
The adsorption performance and photocatalytic activity of the composite adsorption-photocatalyst are significantly improved, and it can efficiently treat antibiotic organic pollutants in high-salt organic wastewater. The reaction conditions are mild, the treatment efficiency is high and the time is short.
Smart Images

Figure CN116920780B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a composite adsorption-photocatalyst and a preparation method thereof, belonging to the technical field of photocatalytic materials. Background Art
[0002] High-salt organic wastewater mainly refers to organic wastewater with a total dissolved solids (TDS) mass fraction of more than 3.5%. The salt substances contained in this type of wastewater are mostly alkali metal salts and Cl - 、SO4 2- Mg 2+ , Ca 2+ Etc. There are many types of high-salt organic wastewater, representative of which are pharmaceutical production wastewater, oil extraction wastewater, printing and dyeing wastewater, leather wastewater, food processing wastewater and landfill leachate. As a highly efficient and energy-saving green chemical technology, photocatalytic technology has important application prospects in the fields of energy and environment. The use of photocatalytic degradation to treat high-salt organic wastewater has also received widespread attention. Graphene-like carbon nitride (g-C3N4) has become a research hotspot in the field of photocatalysis due to its low cost, easy preparation, good stability, and unique physical and chemical properties. However, it still has problems such as low visible light absorption, rapid recombination of photogenerated electron-hole pairs, and relatively low surface area. Therefore, improving the catalytic performance of g-C3N4 photocatalyst is the focus of current research on photocatalytic water treatment technology and the key to its development.
[0003] In order to enhance the visible light response range of g-C3N4 photocatalyst and the separation efficiency of photogenerated electron-hole pairs, reduce the band gap (Eg = 2.7eV), and improve the interface charge transfer efficiency, the g-C3N4 photocatalyst can be surface modified. Doping with non-metallic elements O and P can reduce the band gap of g-C3N4 photocatalyst and increase the specific surface area; Patent application CN114602528A discloses a ternary composite material of cadmium sulfide / indium oxide / phosphorus oxygen doped carbon nitride and its preparation method and application, wherein the composite material realizes the band gap regulation of carbon nitride by doping with phosphorus and oxygen, and the ternary composite material forms a three-dimensional electric field space, which is conducive to the efficient migration and separation of photogenerated electrons and holes; the ternary composite material has a good photodegradation effect on common environmental pollutants such as rhodamine B and methyl orange, and has a good visible light reduction performance on Cr(VII). However, non-metal doped modified g-C3N4 photocatalysts still have defects such as narrow visible light response range, low separation efficiency of photogenerated electron-hole pairs, and low efficiency of improving interfacial charge transfer, and their photocatalytic activity still needs to be further improved. Summary of the invention
[0004] In view of the defects existing in the prior art, one of the purposes of the present invention is to provide a composite adsorption-photocatalyst, wherein the composite adsorption-photocatalyst is co-doped with metal element Fe and non-metal elements O and P into graphene-like carbon nitride, giving full play to the synergistic effect of metal element Fe and non-metal O and P, thereby enhancing the adsorption performance of the composite adsorption-photocatalyst, further reducing the band gap of the composite adsorption-photocatalyst, adjusting the electronic structure, enhancing the photogenerated electron transfer efficiency and the visible light response range, thereby improving the photocatalytic activity of the composite adsorption-photocatalyst;
[0005] The second purpose of the present invention is to provide a method for preparing a composite adsorption-photocatalyst.
[0006] The objectives of the present invention are achieved through the following technical solutions.
[0007] A composite adsorption-photocatalyst, the composite adsorption-photocatalyst has graphene-like carbon nitride (g-C3N4) as a matrix, and three elements of iron, oxygen and phosphorus are co-doped in the matrix; wherein the doping amount of the iron element is 0.8% to 7% of the matrix mass, the doping amount of the oxygen element is 12% to 33% of the matrix mass, and the doping amount of the phosphorus element is 1.4% to 10% of the matrix mass; the bandgap width of the composite adsorption-photocatalyst is 2.1eV to 2.6eV.
[0008] Preferably, the doping amount of iron element is 0.87% to 5.39% of the matrix mass, the doping amount of oxygen element is 13.28% to 32.66% of the matrix mass, and the doping amount of phosphorus element is 1.42% to 8.72% of the matrix mass; the band gap width of the composite adsorption-photocatalyst is 2.14eV to 2.46eV.
[0009] Preferably, the composite adsorption-photocatalyst can adsorb and degrade antibiotic organic pollutants in high-salinity organic wastewater under the irradiation of visible light;
[0010] In the high-salt organic wastewater, the mass of antibiotic organic pollutants and the mass of salts are 1:100; wherein the salts contain Cl - 、SO4 2- Mg 2+ or Ca 2+ Soluble inorganic salts;
[0011] The mass ratio of the composite adsorption-photocatalyst to the organic pollutant is 5:1 to 50:1.
[0012] A method for preparing the composite adsorption-photocatalyst of the present invention, the method steps are as follows:
[0013] (1) adding polyvinyl pyrrolidone (PVP), hexachlorocyclotriphosphazene (HCCP) and ferric nitrate nonahydrate to deionized water under stirring, mixing evenly, then adding melamine, and continuing to stir evenly to obtain a mixed solution;
[0014] Wherein, the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is (0.0001-0.001):(0.1-1.5):(0.4-4.4):(6-7);
[0015] Preferably, the polyvinyl pyrrolidone is prepared into a dispersion liquid with a mass fraction of 0.1% to 0.15% and added, and the solvent of the dispersion liquid is deionized water;
[0016] Preferably, the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is (0.0005-0.001):(0.17-0.75):(1.51-3.03):(6.30-7);
[0017] (2) stirring the mixed solution obtained in step (1) at a constant temperature of 70° C. to 100° C. for 3 h to 5 h, evaporating deionized water to obtain a wet solid; then drying the wet solid at 70° C. to 100° C. to obtain the crude composite adsorption-photocatalyst;
[0018] Preferably, the drying method is vacuum drying, and the drying time is 6h to 12h;
[0019] (3) The crude composite adsorption-photocatalyst obtained in step (2) is fully ground and then calcined at a temperature of 300° C. to 700° C. and a heating rate of 4 to 10° C. min. -1 , calcined for 3h to 5h to obtain the composite adsorption-photocatalyst.
[0020] Beneficial Effects
[0021] (1) The present invention provides a composite adsorption-photocatalyst, which has stable properties. After P doping the g-C3N4 photocatalyst, the valence electrons on the 2p energy level cause the band gap to narrow; O doping increases the specific surface area of g-C3N4, forms a porous structure, and enhances the visible light adsorption effect; Fe doping causes charge transfer between the conduction band or the valence band, which can excite photons with longer wavelengths and lower energy, causing the absorption band edge of the g-C3N4 photocatalyst to red-shift, that is, broadening the response range of the g-C3N4 absorption spectrum, extending the corresponding wavelength of the g-C3N4 photocatalyst to visible light, enhancing the photogenerated electron separation efficiency, and thus improving the photogenerated electron utilization efficiency; Fe and O and P elements show good synergistic effects when co-doped, enhancing the adsorption performance of the composite adsorption-photocatalyst, and further reducing the band gap of the material, adjusting the electronic structure of the material, and enhancing the photogenerated electron transfer efficiency, thereby improving the photocatalytic activity.
[0022] (2) The present invention provides a composite adsorption-photocatalyst, which can achieve efficient treatment of antibiotic organic pollutants in high-salt organic wastewater under the irradiation of visible light. The reaction conditions are mild, the operation is simple, the treatment efficiency is high and the time consumption is short.
[0023] (3) The present invention provides a method for preparing a composite adsorption-photocatalyst, which uses melamine as a raw material, ferric nitrate nonahydrate as a doping metal source, polyvinyl pyrrolidone and hexachlorocyclotriphosphazene as doping non-metal sources, adopts a one-step thermal polymerization method to achieve co-doping, and then obtains the composite adsorption-photocatalyst after calcination; the amount of each substance and the calcination conditions must be strictly controlled in the method: the doping ratio of Fe and P directly affects the adsorption effect and photocatalytic effect of the composite adsorption-photocatalyst, and the calcination time and temperature affect the g-C3N4 band gap, thereby affecting the photocatalytic performance of the composite adsorption-photocatalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are the XRD characterization curves of the composite adsorption-photocatalyst described in Example 1 and the photocatalyst described in Comparative Example 1.
[0025] Figure 2 The fluorescence spectra of the composite adsorption-photocatalyst described in Example 1 and the photocatalyst described in Comparative Example 1 are shown.
[0026] Figure 3 The UV-visible absorption spectra (UV-vis) of the composite adsorption-photocatalyst described in Example 1 and the photocatalyst described in Comparative Example 1 are shown in Figure (a), wherein Figure (b) is a UV-visible spectrum diagram and Figure (b) is a Kubelka-Munk curve.
[0027] Figure 4 This is the full X-ray photoelectron spectroscopy (XPS) spectrum of the composite adsorption-photocatalyst described in Example 1.
[0028] Figure 5 This is a scanning electron microscope (SEM) image of the composite adsorption-photocatalyst described in Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings and specific embodiments. The methods are conventional methods unless otherwise specified, and the raw materials can be obtained from public commercial channels unless otherwise specified.
[0030] In the following comparative examples and embodiments:
[0031] (1) The X-ray diffraction pattern (XRD) of the photocatalyst was tested using a Nissan instrument Ultima IV and the crystal phase and grain size were analyzed. -1 Speed scanning, scanning range is 10~80°.
[0032] (2) Fluorescence spectrum test: The test instrument is FL-7000 fluorescence spectrometer.
[0033] (3) Bandgap calculation: The bandgap is calculated by testing the UV-visible light absorption spectrum of the photocatalyst. The testing instrument is Beijing Puxi General Instrument TU-1901; during the test, first fill the sample stage with barium sulfate for baseline correction and then fill the sample stage with barium sulfate, weigh 10 mg of the photocatalyst and place it on the surface of the sample stage, grind it flat and test it.
[0034] (4) X-ray photoelectron spectroscopy (XPS) test: X-ray photoelectron spectroscopy analysis of the surface electronic state was performed using a PHI 5000 VersaProbe instrument III and a monochromatic Al Kα X-ray source (beam diameter of 200 μm).
[0035] (5) The calculation method of the degradation efficiency is:
[0036] Degradation efficiency (%) = concentration of organic pollutants in high-salinity wastewater after degradation / initial concentration of organic pollutants in high-salinity wastewater × 100%.
[0037] Example 1
[0038] A method for preparing a composite photocatalyst, the method steps are as follows:
[0039] (1) Under stirring conditions, 0.5 mL of a 0.1% aqueous solution of polyvinyl pyrrolidone (PVP), 0.35 g of hexachlorocyclotriphosphazene (HCCP) and 1.5149 g of ferric nitrate nonahydrate were added to deionized water, mixed evenly, and then 6.306 g of melamine was added, and stirring was continued to obtain a mixed solution;
[0040] Among them, the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is 0.0005:0.35:1.5149:6.306;
[0041] (2) stirring the mixed solution obtained in step (1) at a constant temperature of 75° C. for 4 hours, evaporating deionized water to obtain a wet solid; and then vacuum drying the wet solid at 75° C. for 8 hours to obtain a crude composite photocatalyst;
[0042] (3) The crude composite photocatalyst obtained in step (2) was fully ground and then calcined at a temperature of 550°C and a heating rate of 8°C / min. -1 , calcined for 4 hours to obtain a composite photocatalyst.
[0043] The composite photocatalyst prepared in Example 1 was subjected to XRD test, and the results were as follows: Figure 1 As shown, a characteristic peak of graphene-like carbon nitride appears at a 2θ angle of 27°, indicating that the matrix in the composite photocatalyst is graphene-like carbon nitride.
[0044] The composite photocatalyst prepared in Example 1 was tested by SEM, and the results are as follows: Figure 5 As shown, it is explained that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0045] The composite photocatalyst prepared in Example 1 was characterized by XPS. Figure 4 As shown, it can be seen from the XPS full spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis show that in the composite photocatalyst, the doping amount of iron element is 1.27% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 19.38% of the mass of the matrix, and the doping amount of phosphorus element is 2.78% of the mass of the matrix, and the band gap width of the photocatalyst is 2.14eV.
[0046] In summary, the composite photocatalyst prepared in Example 1 is the composite adsorption-photocatalyst of the present invention, and the method can successfully prepare the composite adsorption-photocatalyst of the present invention.
[0047] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0048] The antibiotic organic pollutant is tetracycline;
[0049] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, and the salt is sodium chloride;
[0050] The mass ratio of tetracycline to sodium chloride is 1:100;
[0051] The mass ratios of the composite adsorption-photocatalyst and tetracycline are 5:1, 15:1, 30:1, and 50:1, respectively;
[0052] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0053] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of sodium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0054] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in four beakers, and 10 mg, 30 mg, 60 mg, and 100 mg of the composite adsorption-photocatalyst described in Example 1 were weighed and added to the beakers respectively; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0055] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out, and the concentration of the degradation products was measured using gas chromatography (GC) to calculate the degradation efficiency.
[0056] The results of the degradation efficiency of tetracycline in high-salt organic wastewater by the composite adsorption-photocatalyst of different masses are shown in Table 1.
[0057] Table 1 Degradation efficiency of tetracycline in high-salt organic wastewater by composite adsorption-photocatalysts of different masses
[0058]
[0059] As shown in Table 1, when the mass ratio of the composite adsorption-photocatalyst to the antibiotic pollutants in the high-salt organic wastewater is 5:1 to 50:1, the degradation efficiency of tetracycline increases with the increase in the treatment amount of the composite adsorption-photocatalyst. Within half an hour in the dark, the composite adsorption-photocatalyst still has a significant degradation effect on tetracycline, indicating that the composite adsorption-photocatalyst has a good adsorption effect; when the mass ratio of the composite adsorption-photocatalyst to the antibiotic pollutants in the high-salt organic wastewater is above 30:1, the degradation efficiency of tetracycline can reach more than 90% after first dark treatment for 0.5h and then light treatment for 2h.
[0060] Example 2
[0061] Example 2 is based on Example 1, except that the calcination temperature in step (3) is replaced from "550°C" to "650°C", and the calcination time is replaced from "4h" to "3h", while other conditions remain unchanged, to obtain a composite photocatalyst.
[0062] The composite photocatalyst prepared in Example 2 was subjected to an XRD test, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is a graphene-like carbon nitride structure.
[0063] The oxygen-phosphorus co-doped graphene-like carbon nitride material prepared in Example 2 was subjected to SEM testing, and the results were similar to those in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0064] The composite photocatalyst prepared in Example 2 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.15% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 15.64% of the mass of the matrix, and the doping amount of phosphorus element is 2.07% of the mass of the matrix. The band gap width of the photocatalyst is 2.46 eV.
[0065] In summary, the composite photocatalyst prepared in Example 2 is the composite adsorption-photocatalyst of the present invention, and the method can successfully prepare the composite adsorption-photocatalyst of the present invention.
[0066] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0067] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is sodium sulfate, and the mass ratio of tetracycline to sodium sulfate is 1:100;
[0068] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 30:1;
[0069] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0070] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of sodium sulfate, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0071] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 60 mg of the composite adsorption-photocatalysis described in Example 2 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0072] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0073] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 46.41%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 85.37%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0074] Example 3
[0075] Example 3 is based on Example 1, except that the calcination temperature in step (3) is replaced from "550°C" to "450°C", and the calcination time is replaced from "4h" to "5h", while other conditions remain unchanged, to obtain a composite photocatalyst.
[0076] The composite photocatalyst prepared in Example 3 was subjected to an XRD test, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is graphene-like carbon nitride.
[0077] The oxygen-phosphorus co-doped graphene-like carbon nitride material prepared in Example 3 was subjected to SEM testing, and the results were similar to those in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0078] The composite photocatalyst prepared in Example 3 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.19% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 16.43% of the mass of the matrix, and the doping amount of phosphorus element is 2.12% of the mass of the matrix. The band gap width of the photocatalyst is 2.41eV.
[0079] In summary, the composite photocatalyst prepared in Example 3 is the composite adsorption-photocatalyst described in the present invention, and the method can successfully prepare the composite adsorption-photocatalyst described in the present invention.
[0080] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0081] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is sodium sulfate, and the mass ratio of tetracycline to sodium sulfate is 1:100;
[0082] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 30:1;
[0083] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0084] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of sodium sulfate, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0085] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers containing 2 mg of tetracycline, and 60 mg of the composite adsorption-photocatalyst described in Example 3 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0086] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0087] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 48.13%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 86.53%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0088] Example 4
[0089] Example 4 is based on Example 1 only, and the calcination heating rate in step (3) is changed from "8 ° C. min -1 " is replaced by "4℃·min -1 ", other conditions remain unchanged, and the composite photocatalyst is obtained.
[0090] The composite photocatalyst prepared in Example 4 was subjected to an XRD test, and the result was similar to that in Example 1, indicating that the matrix in the composite photocatalyst was graphene-like carbon nitride.
[0091] The oxygen-phosphorus co-doped graphene-like carbon nitride material prepared in Example 4 was subjected to SEM testing, and the results were similar to those in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0092] The composite photocatalyst prepared in Example 4 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.22% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 17.54% of the mass of the matrix, and the doping amount of phosphorus element is 2.36% of the mass of the matrix. The band gap width of the photocatalyst is 2.27 eV.
[0093] In summary, the composite photocatalyst prepared in Example 4 is the composite adsorption-photocatalyst of the present invention, and the method can successfully prepare the composite adsorption-photocatalyst of the present invention.
[0094] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0095] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is sodium chloride, and the mass ratio of tetracycline to sodium chloride is 1:100;
[0096] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 30:1;
[0097] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0098] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of sodium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0099] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 60 mg of the composite adsorption-photocatalysis described in Example 4 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0100] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0101] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 49.74%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 88.36%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0102] Example 5
[0103] Example 5 is based on Example 1 only, and the calcination heating rate in step (3) is changed from "8 ° C. min -1 " is replaced by "10℃·min -1 ", other conditions remain unchanged, and the composite photocatalyst is obtained.
[0104] The composite photocatalyst prepared in Example 5 was subjected to XRD test, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is graphene-like carbon nitride.
[0105] The composite photocatalyst prepared in Example 5 was subjected to SEM test, and the result was similar to that in Example 1, indicating that the surface morphology of the composite photocatalyst was a porous layered stacking structure.
[0106] The composite photocatalyst prepared in Example 5 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.19% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 17.13% of the mass of the matrix, and the doping amount of phosphorus element is 2.21% of the mass of the matrix. The band gap width of the photocatalyst is 2.35 eV.
[0107] In summary, the composite photocatalyst prepared in Example 5 is the composite adsorption-photocatalyst of the present invention, and the method can successfully prepare the composite adsorption-photocatalyst of the present invention.
[0108] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0109] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is sodium chloride, and the mass ratio of tetracycline to sodium chloride is 1:100;
[0110] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 30:1;
[0111] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0112] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of sodium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0113] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 60 mg of the composite adsorption-photocatalysis described in Example 5 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0114] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0115] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 48.51%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 87.85%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0116] Example 6
[0117] Example 6 is based on Example 1, except that the amount of ferric nitrate nonahydrate in step (1) is replaced by "1.5149 g" to "0.4040 g", wherein the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is 0.0005:0.35:0.4040:6.306, and other conditions remain unchanged, to obtain a composite photocatalyst.
[0118] The composite photocatalyst prepared in Example 6 was subjected to XRD test, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is graphene carbon nitride.
[0119] The composite photocatalyst prepared in Example 6 was subjected to SEM test, and the result was similar to that in Example 1, indicating that the surface morphology of the composite photocatalyst was a porous layered stacking structure.
[0120] The composite photocatalyst prepared in Example 6 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 0.87% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 13.45% of the mass of the matrix, and the doping amount of phosphorus element is 1.97% of the mass of the matrix. The band gap width of the photocatalyst is 2.44 eV.
[0121] In summary, the composite photocatalyst prepared in Example 6 is the composite adsorption-photocatalyst of the present invention, and the method can successfully prepare the composite adsorption-photocatalyst of the present invention.
[0122] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0123] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is magnesium chloride, and the mass ratio of tetracycline to magnesium chloride is 1:100;
[0124] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 50:1;
[0125] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0126] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of magnesium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0127] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 100 mg of the composite adsorption-photocatalysis described in Example 6 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0128] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0129] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 49.37%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 87.15%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0130] Example 7
[0131] Example 7 is based on Example 1, except that the amount of ferric nitrate nonahydrate in step (1) is replaced by "3.03 g" from "1.5149 g", wherein the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is 0.0005:0.35:3.03:6.306, and other conditions remain unchanged, to obtain a composite photocatalyst.
[0132] The composite photocatalyst prepared in Example 7 was subjected to XRD test, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is graphene-like carbon nitride.
[0133] The oxygen-phosphorus co-doped graphene-like carbon nitride material prepared in Example 7 was subjected to SEM testing, and the results were similar to those in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0134] The composite photocatalyst prepared in Example 7 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 2.85% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 32.66% of the mass of the matrix, and the doping amount of phosphorus element is 5.64% of the mass of the matrix. The band gap width of the photocatalyst is 2.45 eV.
[0135] In summary, the composite photocatalyst prepared in Example 7 is a composite adsorption-photocatalyst described in the present invention, and the method can successfully prepare the composite adsorption-photocatalyst described in the present invention.
[0136] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0137] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is magnesium chloride, and the mass ratio of tetracycline to magnesium chloride is 1:100;
[0138] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 50:1;
[0139] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0140] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of magnesium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0141] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 100 mg of the composite adsorption-photocatalysis described in Example 7 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0142] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0143] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 49.78%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 87.09%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0144] Example 8
[0145] Example 8 is based on Example 1 only, except that the amount of hexachlorocyclotriphosphazene (HCCP) in step (1) is replaced from "0.35 g" to "0.17 g", wherein the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is 0.0005:0.17:1.5149:6.306;
[0146] In step (2), the obtained mixed solution "stirring at a constant temperature of 75°C for 4 hours" is replaced by "stirring at a constant temperature of 100°C for 3 hours", and other conditions remain unchanged to obtain a composite photocatalyst.
[0147] The composite photocatalyst prepared in Example 8 was subjected to XRD testing, and the result was similar to that in Example 1, indicating that the matrix in the composite photocatalyst was graphene-like carbon nitride.
[0148] The oxygen-phosphorus co-doped graphene-like carbon nitride material prepared in Example 8 was subjected to SEM testing, and the results were similar to those in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0149] The composite photocatalyst prepared in Example 8 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.06% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 13.28% of the mass of the matrix, and the doping amount of phosphorus element is 1.42% of the mass of the matrix. The band gap width of the photocatalyst is 2.34 eV.
[0150] In summary, the composite photocatalyst prepared in Example 8 is a composite adsorption-photocatalyst described in the present invention, and the method can successfully prepare the composite adsorption-photocatalyst described in the present invention.
[0151] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0152] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is magnesium chloride, and the mass ratio of tetracycline to magnesium chloride is 1:100;
[0153] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 30:1;
[0154] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0155] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of magnesium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0156] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 60 mg of the composite adsorption-photocatalysis described in Example 8 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0157] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0158] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 49.21%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 88.03%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0159] Example 9
[0160] Example 9 is based on Example 1, except that the amount of hexachlorocyclotriphosphazene (HCCP) in step (1) is replaced by "0.75 g" from "0.35 g", wherein the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is 0.0005:0.75:1.5149:6.306;
[0161] In step (2), the obtained mixed solution "stirred at a constant temperature of 75°C for 4 hours" was replaced by "stirred at a constant temperature of 70°C for 5 hours", and other conditions remained unchanged to obtain a composite photocatalyst.
[0162] The composite photocatalyst prepared in Example 9 was subjected to XRD testing, and the result was similar to that in Example 1, indicating that the matrix in the composite photocatalyst was graphene-like carbon nitride.
[0163] The composite photocatalyst prepared in Example 9 was subjected to SEM test, and the result was similar to that in Example 1, indicating that the surface morphology of the composite photocatalyst was a porous layered stacking structure.
[0164] The composite photocatalyst prepared in Example 9 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 5.39% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 31.29% of the mass of the matrix, and the doping amount of phosphorus element is 8.72% of the mass of the matrix. The bandgap width of the photocatalyst is 2.17 eV.
[0165] In summary, the composite photocatalyst prepared in Example 9 is a composite adsorption-photocatalyst described in the present invention; and the method can successfully prepare the composite adsorption-photocatalyst described in the present invention.
[0166] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0167] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is magnesium chloride, and the mass ratio of tetracycline to magnesium chloride is 1:100;
[0168] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 15:1;
[0169] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0170] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 mg of magnesium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0171] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 30 mg of the composite adsorption-photocatalysis described in Example 9 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0172] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0173] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 42.56%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 82.71%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0174] Example 10
[0175] Example 10 is based only on Example 1, except that the "0.1% by mass% polyvinyl pyrrolidone (PVP) 0.0005 g" in step (1) is replaced by "0.15% by mass% polyvinyl pyrrolidone (PVP) 0.001 g", and the "the solid is vacuum dried at 75°C for 8 h" in step (2) is replaced by "the solid is vacuum dried at 100°C for 6 h", and other conditions remain unchanged to obtain a composite photocatalyst.
[0176] The composite photocatalyst prepared in Example 10 was subjected to XRD testing, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is graphene-like carbon nitride.
[0177] The composite photocatalyst prepared in Example 10 was subjected to SEM testing, and the result was similar to that in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0178] The composite photocatalyst prepared in Example 10 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.04% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 18.57% of the mass of the matrix, and the doping amount of phosphorus element is 2.49% of the mass of the matrix. The band gap width of the photocatalyst is 2.26 eV.
[0179] In summary, the composite photocatalyst prepared in Example 10 is a composite adsorption-photocatalyst described in the present invention; and the method can successfully prepare the composite adsorption-photocatalyst described in the present invention.
[0180] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0181] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is calcium chloride, and the mass ratio of tetracycline to calcium chloride is 1:100;
[0182] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 30:1;
[0183] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0184] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 mg of calcium chloride, and after complete dissolution, add to a 1 L volumetric flask to obtain a target pollutant solution;
[0185] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 60 mg of the composite adsorption-photocatalysis described in Example 10 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0186] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0187] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 51.37%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 89.81%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0188] Embodiment 11
[0189] Example 11 is based on Example 1, except that the amount of melamine in step (1) is replaced from "6.306 g" to "7 g", and "the solid is vacuum dried at 75°C for 8 h" in step (2) is replaced by "the solid is vacuum dried at 70°C for 12 h", and other conditions remain unchanged to obtain a composite photocatalyst.
[0190] The composite photocatalyst prepared in Example 11 was subjected to XRD testing, and the result was similar to that in Example 1, indicating that in the composite photocatalyst, the matrix is graphene-like carbon nitride.
[0191] The composite photocatalyst prepared in Example 11 was subjected to SEM testing, and the result was similar to that in Example 1, indicating that the surface morphology of the composite photocatalyst is a porous layered stacking structure.
[0192] The composite photocatalyst prepared in Example 11 was characterized by XPS, and the results were similar to those in Example 1. It can be seen from the full XPS spectrum that the three elements of iron, oxygen and phosphorus are co-doped in the matrix g-C3N4; and further XPS testing and analysis showed that in the composite photocatalyst, the doping amount of iron element is 1.12% of the mass of the matrix (graphene-like carbon nitride), the doping amount of oxygen element is 18.79% of the mass of the matrix, and the doping amount of phosphorus element is 2.54% of the mass of the matrix. The band gap width of the photocatalyst is 2.18 eV.
[0193] In summary, the composite photocatalyst prepared in Example 11 is a composite adsorption-photocatalyst described in the present invention, and the method can successfully prepare the composite adsorption-photocatalyst described in the present invention.
[0194] A composite adsorption-photocatalyst according to this embodiment, wherein the composite adsorption-photocatalyst is used for adsorption-degradation of antibiotic organic pollutants in high-salinity organic wastewater;
[0195] In the high-salt organic wastewater, the antibiotic organic pollutant is tetracycline, the salt is calcium chloride, and the mass ratio of tetracycline to calcium chloride is 1:100;
[0196] The mass ratio of the composite adsorption-photocatalyst to tetracycline is 15:1;
[0197] Specifically, the steps of composite adsorption-photocatalyst photocatalytic adsorption-degradation are as follows:
[0198] (1) Weigh 40 mg of tetracycline, add 100 mL of deionized water and stir to dissolve, then add 4 g of calcium chloride, and after complete dissolution, add to a 1 L volumetric flask to make up to volume to obtain a target pollutant solution;
[0199] (2) 50 mL of the target pollutant solution (containing 2 mg of tetracycline) was measured and placed in 4 beakers respectively, and 30 mg of the composite adsorption-photocatalysis described in Example 2 was weighed and added to the beakers; the beakers were placed in a photocatalytic box and the magnetic stirrer was turned on;
[0200] (3) After half an hour of darkness, a 300 W xenon lamp was turned on for degradation for 0.5 h, 1 h, 1.5 h, and 2 h, respectively. After the degradation was completed, the light source was turned off to complete the degradation. The degradation products were taken out and measured by gas chromatography (GC) to calculate the degradation efficiency.
[0201] The test results show that the degradation efficiency of tetracycline by the composite adsorption-photocatalyst under dark conditions for 0.5h is 42.37%, indicating that the composite adsorption-photocatalyst has a good adsorption effect; after 2h of light treatment, the degradation efficiency of tetracycline can reach 82.26%, indicating that the composite adsorption-photocatalyst exhibits excellent photocatalytic degradation performance for tetracycline.
[0202] Comparative Example 1
[0203] Comparative Example 1 is a pure C3N4 photocatalyst.
[0204] 3 g of melamine was placed in a crucible and calcined in a muffle furnace at a temperature of 550 °C and a heating rate of 8 °C min. -1 , the calcination time is 4h, and pure C3N4 photocatalyst is obtained.
[0205] The pure C3N4 photocatalyst prepared in Comparative Example 1 was characterized by XRD. Figure 1 As shown, a characteristic peak of graphene-like carbon nitride appears at a 2θ angle of 27°, indicating that the pure C3N4 is a g-C3N4 structure.
[0206] The composite adsorption-photocatalyst prepared in Example 1 and the pure C3N4 photocatalyst prepared in Comparative Example 1 were tested for fluorescence spectra. The results are as follows: Figure 2 As shown, the lower the fluorescence intensity, the lower the probability of electron-hole pair recombination and the stronger the photocatalytic performance. The fluorescence intensity of the composite adsorption-photocatalyst described in Example 1 is significantly lower than that of the pure C3N4 described in Comparative Example 1, indicating that doping is beneficial to enhancing the photocatalytic performance of g-C3N4; the test results of Examples 2 to 11 are similar to those of Example 1.
[0207] The composite adsorption-photocatalyst prepared in Example 1 and the pure C3N4 photocatalyst prepared in Comparative Example 1 were tested by ultraviolet spectroscopy. The results are as follows: Figure 3As shown, the band gap width of the composite adsorption-photocatalyst described in Example 1 is significantly lower than the band gap width of the pure C3N4 photocatalyst described in Comparative Example 1, and can absorb more wavelengths of light, thereby improving the light absorption rate and having stronger photocatalytic activity; the test results of Examples 2 to 11 are similar to those of Example 1.
[0208] The specific surface area and pore size of the composite adsorption-photocatalyst prepared in Example 1 and the pure C3N4 photocatalyst prepared in Comparative Example 1 were tested. The test results show that the specific surface area of the composite adsorption-photocatalyst in Example 1 is 70.202 m 2 / g, pore volume is 0.137cm 3 / g, and the pore size is 7.783nm; while the specific surface area of the pure C3N4 photocatalyst prepared in Comparative Example 1 is only 33.246m 2 / g, pore volume is 0.081cm 3 / g, and the pore size is 9.755nm; this shows that the composite adsorption-photocatalyst described in Example 1 has a larger specific surface area and pore volume than the pure C3N4 in Comparative Example 1, which is beneficial to enhancing the adsorption capacity of the material; the test results of Examples 2 to 11 are similar to those of Example 1.
[0209] In summary, the invention includes but is not limited to the above embodiments. Any equivalent substitution or partial improvement made under the spirit and principle of the invention shall be deemed to be within the protection scope of the invention.
Claims
1. Application of a composite adsorption-photocatalyst in the degradation of antibiotic organic pollutants, characterized in that: The composite adsorption-photocatalyst is based on graphene-like carbon nitride, and three elements of iron, oxygen and phosphorus are co-doped in the matrix; wherein the doping amount of the iron element is 0.8% to 7% of the matrix mass, the doping amount of the oxygen element is 12% to 33% of the matrix mass, and the doping amount of the phosphorus element is 1.4% to 10% of the matrix mass; the band gap width of the composite adsorption-photocatalyst is 2.1eV to 2.6eV; the co-doping of the three elements of iron, oxygen and phosphorus adjusts the electronic structure of the catalyst and enhances the efficiency of photogenerated electron transfer; The composite adsorption-photocatalyst is prepared by the following method, and the steps of the method are as follows: (1) adding polyvinyl pyrrolidone, hexachlorocyclotriphosphazene and ferric nitrate nonahydrate to deionized water under stirring, mixing evenly, then adding melamine, and continuing to stir evenly to obtain a mixed solution; Among them, the mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is (0.0001~0.001): (0.1~1.5): (0.4~4.4): (6~7); (2) stirring the mixed solution at a constant temperature of 70° C. to 100° C. for 3 h to 5 h, evaporating deionized water to obtain a wet solid; and then drying the wet solid at 70° C. to 100° C. to obtain the crude composite adsorption-photocatalyst; (3) Grinding the crude composite adsorption-photocatalyst product and calcining it at a temperature of 300°C to 700°C and a heating rate of 4 to 10°C min -1 , calcining for 3h~5h to obtain the composite adsorption-photocatalyst; The composite adsorption-photocatalyst can adsorb and degrade antibiotic organic pollutants in high-salt organic wastewater under the irradiation of visible light; In the high-salt organic wastewater, the mass of antibiotic organic pollutants and the mass of salts are 1:100; wherein the salts contain Cl - 、SO4 2- Mg 2+ or Ca 2+ Soluble inorganic salts; The mass ratio of the composite adsorption-photocatalyst to the antibiotic organic pollutant is 5:1 to 50:1; The antibiotic organic pollutant is tetracycline.
2. The use according to claim 1, characterized in that: The doping amount of iron element is 0.87%~5.39% of the matrix mass, the doping amount of oxygen element is 13.28%~32.66% of the matrix mass, and the doping amount of phosphorus element is 1.42%~8.72% of the matrix mass; the band gap width of the composite adsorption-photocatalyst is 2.14eV~2.46eV.
3. The use according to claim 1, characterized in that: The mass ratio of PVP, HCCP, ferric nitrate nonahydrate and melamine is (0.0005~0.001):(0.17~0.75):(1.51~3.03):(6.30~7).
4. The use according to claim 1, characterized in that: The polyvinyl pyrrolidone is prepared into a dispersion with a mass fraction of 0.1% to 0.15% and added, the solvent of the dispersion is deionized water; the drying method is vacuum drying, and the drying time is 6h to 12h.
Citation Information
Patent Citations
Phosphorus-doped porous hierarchical structure carbon nitride photocatalyst as well as preparation method and application thereof
CN115069286A